Dokument fundacyjny klasztoru Kanoników Regularnych Laterańskich w Kraśniku - Bielak, Włodzimierz (Archiwa, Biblioteki i Muzea Kościelne, 2017)
The paper presents the critical edition of the foundation document of the monastery of the Canons Regular of the Lateran in Kraśnik, issued by Jan Rabsztyński (the Topór coat of arms) on18 May 1468. In this document the founder asks the Bishop of Cracow Jan Lutek of Brzezia to transform the parish church in Kraśnik into a monastic church of the Canons Regular. The article includes the detailed description of the monastery’s emoluments. The drawer of the document showed the links between the Kraśnik monastery and the Corpus Christi Monastery in Cracow.